Emotion state of operator subjected by electromagnetic noise radiation - A. V. Sidorenko; N. A. Solodyuho (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The experimental investigations of operator electroencephalograms subjected by electromagnetic noise radiation were carried out. The electroencephalograms were registrated according to international «10/20» system. The numerical parameters as arousal and emotion valence characterized the emotion state of operator were estimated. The definition of these parameters based on spectral power densities of rhythms brain components. These parameters were estimated as developed positive emotions.